Clinical approach to the diagnosis of autoimmune encephalitis in the pediatric patient. Issue 2 (March 2020) - Cellucci, Tania; Van Mater, Heather; Graus, Francesc; Muscal, Eyal; Gallentine, William; Klein-Gitelman, Marisa S.; Benseler, Susanne M.; Frankovich, Jennifer; Gorman, Mark P.; Van Haren, Keith; Dalmau, Josep; Dale, Russell C.
Abstract : Objective: Autoimmune encephalitis (AE) is an important and treatable cause of acute encephalitis. Diagnosis of AE in a developing child is challenging because of overlap in clinical presentations with other diseases and complexity of normal behavior changes. Existing diagnostic criteria for adult AE require modification to be applied to children, who differ from adults in their clinical presentations, paraclinical findings, autoantibody profiles, treatment response, and long-term outcomes. Methods: A subcommittee of the Autoimmune Encephalitis International Working Group collaborated through conference calls and email correspondence to consider the pediatric-specific approach to AE. The subcommittee reviewed the literature of relevant AE studies and sought additional input from other expert clinicians and researchers. Results: Existing consensus criteria for adult AE were refined for use in children. Provisional pediatric AE classification criteria and an algorithm to facilitate early diagnosis are proposed. There is also discussion about how to distinguish pediatric AE from conditions within the differential diagnosis. Conclusions: Diagnosing AE is based on the combination of a clinical history consistent with pediatric AE and supportive diagnostic testing, which includes but is not dependent on antibody testing. The proposed criteria and algorithm require validation in prospective pediatric cohorts.